2021
DOI: 10.21203/rs.3.rs-268749/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOXC10 promotes growth and migration of melanoma by regulating Slug to activate the YAP/TAZ signaling pathway

Abstract: Homeobox C10 (HOXC10) has been reported to participate in various cancers. However, the involvement of HOXC10 in melanoma is still remains unknown. Here, we attempted to determine whether HOXC10 can affect the development of melanoma. We separated melanoma tissues and the matched tumor-adjacent normal tissues from melanoma patients, and examined HOXC10 expression in the melanoma cells and tissues. Comparing with the tumor-adjacent normal tissues, HOXC10 was up-regulated in melanoma tissues. Melanoma cells also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…While Grhl1 has been shown to regulate epidermal homeostasis by controlling the differentiation program and barrier function (Wilanowski et al, 2008), a role in melanoma development has not been reported. Likewise, Slug has been linked to melanoma cell metastasis but not in the creation of a pro-melanoma keratinocyte compartment (Miao et al, 2021; Shirley et al, 2012). Importantly, while increased Slug likely plays additional roles in shaping the early melanoma tumor environment, genetic targeting of Dsg1 is sufficient to initiate the signaling cascade that stimulates increased melanoma cell movement in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…While Grhl1 has been shown to regulate epidermal homeostasis by controlling the differentiation program and barrier function (Wilanowski et al, 2008), a role in melanoma development has not been reported. Likewise, Slug has been linked to melanoma cell metastasis but not in the creation of a pro-melanoma keratinocyte compartment (Miao et al, 2021; Shirley et al, 2012). Importantly, while increased Slug likely plays additional roles in shaping the early melanoma tumor environment, genetic targeting of Dsg1 is sufficient to initiate the signaling cascade that stimulates increased melanoma cell movement in vitro .…”
Section: Discussionmentioning
confidence: 99%